Prácticas de enseñanza de iniciación a la lecto-escritura en inicial II en el Centro de Desarrollo Infantil Dafi Kids - Orozco Orozco, Andrea Viviana (2016)
The present case study explains how teaching techniques are developed with respect to the initiation of the Reading and Writing Skills in children of first year or Elementary School, specifically of Dafi Kids Children Development Centre. It is located in Rumiñahui in the Sangolqui parish. This group has 18 children. In this investigation it was possible to observe six determined categories which are planning, structure of the methodology, organization, teacher/student interaction, evaluation and academic tasks. This observation was made over a period of two months for about six hours a week. For the case studies the ethnographic method was applied, along with techniques and tools of the qualitative method. Among these we can find observation, participant, semi-structured interviews, a field diary and an observation file. Through these, the necessary information was acquired in order to make the analysis, which has been related to theoretical elements about the praxis of the teaching and learning of Reading and Writing Skills.